Advances and applications of biofiber polymer composites in regenerative medicine - Bishi, Dillip Kumar; Mathapati, Santosh; Padhi, Priyadarshini; Venkataprasanna, Kannan Sampath Kumar; Ezhilarasu, Hariharan; Ramalingam, Raghavendra; Mohd Hasbi, Ab Rahim; Venugopal, Jayarama Reddy (Elsevier, 2021)
Tissue engineering is an emerging field to study the principles of medicine, biology, and bioengineering for designing biological substitutes to restore the tissue functions in regenerative medicine. Nanotechnology is a valuable tool to track and image stem cells, to drive their differentiation into specific stem cells and ultimately to understand stem cell biology. Stem cell-based therapeutics lead to the prevention, diagnosis, and treatment of human diseases. The availability of more durable and better prosthetics and new drug delivery systems are of great scientific interest and give hope for cancer treatment and minimally invasive treatments for heart disease, diabetes, and other diseases. Electrospinning is a well-established process capable of producing ultra-fine biofibers over the thickness and porosity of nanofiber meshes. The diameter of polymer shrinks from micrometers (10-100 µm) to nanometers (10-100 nm) with large surface area. Interconnectivity of biofibers is well suited for nutrient transport, cell migration, communication, and efficient cellular responses for developing artificial organs. Stem cells are considered cell-based tissue engineering approaches, of which bone-marrow-derived mesenchymal stem cells, adipose-derived stem cells, adult stem cells and embryonic stem cells are frequently utilized for the advancement of new tissue engineering strategies. The cells are combined with nanotechnology and applied for the regeneration of various tissue systems such as bone, cartilage, nerves, cardiac muscles, and skin. Advances in biotechnological, especially biomedical nanotechnology, applications of polymer nanofibers from the perspective to commercialized stages, collaborative interdisciplinary researches involving surgeons, material scientists, biologist, physiologists, clinicians, and engineers are required to develop functionalized artificial organs in regenerative medicine to benefit people.